Intralesional bleomycin in palmoplantar and periungual warts: a therapeutic study - Devi B., Gayatri; Raju, P. V. Krishnam; Gopal, K. V. T.; Sneha, Vanapalli R. (International Journal of Research in Dermatology, 2021)
Background: Warts are one of the most common benign growths of skin caused by human papilloma virus. No single treatment has proved to be completely effective and most therapies for palmo-plantar and periungual warts remain unsatisfactory. The present study was conducted to evaluate the therapeutic efficacy and safety of intralesional bleomycin injection in palmo-plantar and periungual warts in patients in region of south east India. Methods: Ninety patients of multiple palmo-plantar and periungual warts were included in the study. They were infiltrated with bleomycin (1 mg/ml) till blanching. The treatment was repeated after paring of eschar at 2 weeks interval in cases with partial or no response. The patients were reviewed at monthly interval for 24 weeks to note cure, adverse effects, recurrence and outcome satisfaction levels. Results: Out of total 305 warts, 103 (34%) were cured after 1st injection and 249 (82%) were cured after 2nd injection. The number of warts requiring more than 2 sittings was 55 (18%). At the end of study, overall cure rate was 94.5% and 10 patients showed recurrence. Conclusions: Intralesional bleomycin injection is an effective and safe treatment option in palmo-plantar and periungual warts.